EFEKTIVITAS PASAL 170 KUHP DALAM MENANGANI KEKERASAN KOLEKTIF: STUDI KASUS GENG MOTOR DI KOTA TASIKMALAYA - Muhamad Taufik, Luthfi; Ratno, Dedi (Program Studi Hukum Tata Negara, 2025)
This study aims to examine the criminal law review of perpetrators of motorcycle gang violence in Tasikmalaya City based on Article 170 of the Criminal Code. The phenomenon of motorcycle gangs in Tasikmalaya is a concern because of the increase in violence in public spaces committed collectively by teenagers. The research method used is qualitative with a case study approach at the Tasikmalaya City Resort Police. Data was collected through interviews, observations, and document studies. The results show that law enforcement faces challenges such as a lack of evidence, low community participation, and a lack of preventive approaches. The implementation of Article 170 of the Criminal Code is still repressive without being balanced with a sustainable rehabilitative program. A comprehensive strategy is needed by prioritizing restorative justice, youth education, and collaboration between the police and the community in dealing with violence by motorcycle gangs.